Perceived Patient Safety Culture and Safety Performance among Nurses in a Private Hospital - Punida Sathivheil; Siti Fatimah Md Shariff (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction; Patient safety continues to be a significant challenge for healthcare institutions in the 21st century, as these organizations strive to provide high-quality care. Understanding patient safety culture and its relationship and safety perceptions among nurses is one way to identify potential areas for improvement in patient safety. Therefore, understanding and addressing the real challenges related to safe practices in healthcare settings is essential.Objectives; The objective of this study is to evaluate level of patient safety culture and safety performance among nurses in among nurses in a in the Private Hospital, located in Kedah, Malaysia. Methods; This study employed a quantitative correlational design using a cross-sectional approach. The study population will be 247 nurses from different working unit. The sampling technique used was purposive sampling, a method that selects participants based on specific predetermined criteria. Data collection utilized validated questionnaires on the level of patient safety culture and safety performance. Purposive sampling was used to select participants. Data collection utilized validated questionnaires on safety performance and patient safety culture and analysis will be perform using the chi-square goodness-of-fit test. Results: The study assessed the perceptions of 247 nurses on patient safety culture and safety performance, revealing overwhelmingly positive responses in key areas like safety participation (98.0%), safety compliance (96.8%), and event reporting (91.1%). Moderate positive perceptions were found in teamwork (59.9%), management support (65.2%), and communication openness (57.1%), while lower positive in staffing and perceptions patient safety culture were nearly evenly split (51.4% positive, 48.6% negative). Despite a generally strong safety culture, concerns remain in staffing and overall safety perception, highlighting areas for improvement in healthcare settings. Conclusions: The survey highlights strong nurse participation in safety protocols, emphasizing the need for management focus on patient safety cultural change, continuous improvement, and a patient-centered approach for optimal care.